Face of the Human and Surface of the World: Reflections on Cinematic Pantheism - El Khachab, Walid (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2006)
In this article, the surface of the world is envisaged as a face. Cinema as a record of this surface, and as a medium which “re-invented” the face in the close-up shot, makes it possible to reflect on the status of the human subject in the universe, thanks to the concept of cinematic pantheism. Following Elie Faure, the author underscores the pantheistic nature of cinema and claims that cinematic pantheism is the way by which film produces simultaneously transcendence and immanence, and materializes the unity of both, thus confirming Siegfried Kracauer's theory according to which man, nature and culture are part of the same “visible phenomena” in cinema. Cinema transforms all beings into surfaces: it operates by facialization and surfacialization. On the other hand, the article revisits Deleuze and Guattari's concept of faciality and argues that it describes a surface operating as the interface of the body in its interaction with other bodies in the media, the realm of the divine, or the universe. Thus faciality is also landscapity, and activating the camera means “transfiguring” the human (or the landscape) into face and introducing a vis-a-vis: the face of God, as immanent transcendence. In that sense, cinematic mysticism, as in Paradjanov's, Makhmalbaf's and Mikhalkov's films, is pantheistic.